Peran Analisis Pemanfaatan Situs Jejaring Sosial Facebook Sebagai Media Promosi Situs P-Store.net (Studi Kasus: PT. Trijaya Digital Grup) - Muhammad Priyo Utomo; Nurhidayati Nurhidayati (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The Getting service quality in the marketing field is not only done by physically meeting between customers and service providers, such as conventional market systems. In modern society that wants to be fast and instant, time constraints are the reason for customers to shop in the current system. With a modern marketing system with the application of internet technology called Internet Marketing, time constraints can be minimized. The modern marketing system will shorten the distance between customers and department stores, especially only in home shopping. Satisfied customers will recommend their experience to their community, both in online and face-to-face communities. Studying and analyzing the online store network P-store.net, which is engaged in the business of marketplace services and online transaction security services, produces findings that promotions carried out using social media, namely Facebook, can increase the number of deals or transactions. Qualitative analysis of P-Store.net, there are several important factors, namely: promotional techniques, service quality and the use of facebook social media networks. The results of this study show an increase in the number of users of the P-Store site which has fluctuated in the last five years from 2018 to 2022.